Natural Processes Removing Dissolved Arsenic from Selected West Coast Streams - J Webster-Brown; C Noble (The Australasian Institute of Mining and Metallurgy, 2003)
A survey of selected West Coast Streams was undertaken in Summer 2001, Summer 2002 and Winter 2002 to establish the degree of arsenic (As) contamination in waters and sediments downstream of old coal and gold mine workings on the West Coast. Of the catchments studied, Soldiers/Ford Creek and Rapid Stream showed the most significant elevated As concentrations, predominantly in dissolved form, and evidence of AMD or ARD contamination (high sulfate concentrations and/or acidity). The rate and processes of removal of dissolved arsenic from the water column (attenuation) have been studied in these catchments. The Rapid Stream and Soldiers/Ford Creek catchments are directly affected by adit drainage from the Sullivan and Blackball coal mines respectively. Both catchments have high As concentrations in the sediments, with up to 770 mg/kg in Soldiers Creek and 490 mg/kg in Rapid Stream. Dissolved As concentrations are significantly elevated in the neutral pH waters of Soldiers Creek; typically as high as 100 - 200 ¦g/kg, up to 500 m downstream of the main adit discharge (800 ¦g/kg As). Adit inflows to Rapid Stream were acidic and contained 20 - 30 ¦g/kg dissolved As, with relatively high concentrations of arsenic in the stream water in winter (up to 18 ¦g/kg), but not in summer. Analysis of concentration trends and As:SO4 ratios downstream of these obvious As sources confirmed that dissolved As had been actively removed from the water column, but varied seasonally with greater removal evident in summer. Adsorption of arsenic onto iron oxide in the stream sediments is the most likely mechanism of removal. The Snowy River catchment, on the other hand, has relatively high As concentrations in both the sediments and the water column, but there was little evidence of a distinct AMD or ARD input from the Blackwater gold mining area. Preliminary investigation suggests that dilution rather than attenuation is responsible for decreasing As concentrations downstream.